CORE AND FLEKSIBILITY TRAINING ON MYOGENIC LOW BACK PAIN: A CASE REPORT - Arzhuma Arza Lazuardy; Totok Budi Santoso; Kingkinnarti, Kingkinnarti (Jurnal Cakrawala Ilmiah, 2025)
Myogenic low back pain refers to discomfort arising from stress or strain on the back's muscles, tendons, and ligaments, typically resulting from excessive daily activities. This condition warrants attention due to its potential to cause issues such as lost work time and decreased productivity. Pupose: To determine the implementation of core stability exercise and flexibility training in cases of myogenic lbp pain. Methodes: Research with the Case Report method was conducted at Dr. Harjono Ponorogo Hospotal on a 32-year-old female patient who was diagnosed with myogenic LBP with complaints of low back pain and discomfort during activities. Patients are given an intervention with core stability and flexibility in the form of exercise therapy which is done 1 week 2 times. Result: The exercise therapy which was carried out 3 times resulted in a decrease in pain, an increase in muscle strength, an increase in runk LGS, and increase in functional activity. Conclusion: Physiotherapy intervention in cases myogenic LBP, as a whole the evaluation result found an increase